2002
DOI: 10.1128/mcb.22.4.992-1000.2002
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Activator of NF-κB Ligand (RANKL) Activates TAK1 Mitogen-Activated Protein Kinase Kinase Kinase through a Signaling Complex Containing RANK, TAB2, and TRAF6

Abstract: The receptor activator of NF-B (RANK) and its ligand RANKL are key molecules for differentiation and activation of osteoclasts. RANKL stimulates transcription factors AP-1 through mitogen-activated protein kinase (MAPK) activation, and NF-B through IB kinase (IKK) activation. Tumor necrosis factor receptorassociated factor 6 (TRAF6) is essential for activation of these kinases. In the interleukin-1 signaling pathway, TAK1 MAPK kinase kinase (MAPKKK) mediates MAPK and IKK activation via interaction with TRAF6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
210
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(217 citation statements)
references
References 47 publications
3
210
0
4
Order By: Relevance
“…A 1 R blockade disrupts RANKL-induced formation of TRAF6-TAK1 complex in primary BMMs TAK1, a MAPK kinase kinase can form complexes with RANK and TRAF6, and was up-regulated in RANKLinduced osteoclastogenesis ( [23][24][25]. RANKL-induced osteoclast differentiation requires TAK1 for NF-κB activation [25].…”
Section: A 1 R Blockade Suppresses Osteoclastogenesis and Bone-resorbmentioning
confidence: 99%
See 1 more Smart Citation
“…A 1 R blockade disrupts RANKL-induced formation of TRAF6-TAK1 complex in primary BMMs TAK1, a MAPK kinase kinase can form complexes with RANK and TRAF6, and was up-regulated in RANKLinduced osteoclastogenesis ( [23][24][25]. RANKL-induced osteoclast differentiation requires TAK1 for NF-κB activation [25].…”
Section: A 1 R Blockade Suppresses Osteoclastogenesis and Bone-resorbmentioning
confidence: 99%
“…Another signaling protein, transformation growth factor-β (TGF-β) activated kinase-1 (TAK1) has been implicated in RANKL-induced osteoclastogenesis [23][24][25]. Upon RANK receptor engagement, the cytoplasmic domain of RANK interacts with an adaptor protein, tumor necrosis factor-receptorassociated factor 6 (TRAF6), and endogenous TAK1 is recruited to the TRAF6 complex.…”
Section: Introductionmentioning
confidence: 99%
“…26 TAK1 has been suggested to contribute to NF-kB activation by TNFa and RANKL. 15,27 Therefore, we investigated whether the TAK1-MKK6-p38 pathway is relevant to NF-kB activation by RANKL. We first examined the effect of TAK1-DN on IkB phosphorylation and degradation, steps required for release and nuclear translocation of NF-kB, by RANKL.…”
Section: Tak1-mkk6-p38 Signalling Is Necessary For Nfatc1 Induction Fmentioning
confidence: 99%
“…A study showed that transforming growth factor-beta-activated kinase 1 (TAK1), a MAPKKK, can form complexes with RANK, TRAF6, and TAB2 in RANK-overexpressing 293 cells. 15 The activity of TAK1 was stimulated by RANKL in the RANK-expressing 293 and RAW264.7 cells. 15 However, the effect of TAK1 activation on RANKL-induced Oc differentiation has not been demonstrated.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation